2021
DOI: 10.1155/2021/5548918
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hub Genes to Regulate Breast Cancer Spinal Metastases by Bioinformatics Analyses

Abstract: Breast cancer (BC) had been one of the deadliest types of cancers in women worldwide. More than 65% of advanced-stage BC patients were identified to have bone metastasis. However, the molecular mechanisms involved in the BC spinal metastases remained largely unclear. This study screened dysregulated genes in the progression of BC spinal metastases by analyzing GSE22358. Moreover, we constructed PPI networks to identify key regulators in this progression. Bioinformatics analysis showed that these key regulators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Previous literature suggests that, both in vitro and in vivo , paeoniflorin regulates the migration and invasion of breast cancer cells by down-regulating microrNA-15B through FOXO1/CCND1/β-catenin axis ( 6 ). Previous studies have also indicated that CEP55 was a key regulator in BC spinal metastases by Bioinformatics Analyses ( 11 ). Despite the significant developments and rapid progression in the field of BC with bone metastasis, translation of this information into early detection markers and effective treatments are limited.…”
Section: Introductionmentioning
confidence: 92%
“…Previous literature suggests that, both in vitro and in vivo , paeoniflorin regulates the migration and invasion of breast cancer cells by down-regulating microrNA-15B through FOXO1/CCND1/β-catenin axis ( 6 ). Previous studies have also indicated that CEP55 was a key regulator in BC spinal metastases by Bioinformatics Analyses ( 11 ). Despite the significant developments and rapid progression in the field of BC with bone metastasis, translation of this information into early detection markers and effective treatments are limited.…”
Section: Introductionmentioning
confidence: 92%
“…In an ovarian cancer research, the overexpression of IFI6 could facilitate the multiplication of tumor cells and mediate their chemoresistance [ 15 ]. In addition, IFI6 is regarded as a crucial predictor of poor outcome in breast cancer [ 34 , 38 ]. In the study of hematological tumors, aberrantly expressed IFI6 in multiple myeloma is an important factor leading to the chemoresistance of myeloma cells [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hub genes of the four common signaling pathways were analyzed and WNT1, AKT3, DVL1, CCND1, HIST1H2BO, JUN, EGFR, RAC1, ACTN1 and ACTN2 were screened out. These hub genes are primarily involved in the processes of cell proliferation and differentiation (24)(25)(26)(27)(28)(29)(30)(31). Some genes are also reported to be involved in the formation of osteoclasts (32,33).…”
Section: Discussionmentioning
confidence: 99%